Diversity and morphological characterization of Musa spp. in North Kivu and Ituri provinces, Eastern Democratic Republic of Congo - Sivirihauma, Charles; Ocimati, W.; Valimuzigha, K.; Karamura, D.; Adheka, J.; Ibanda, B.; Dhed’a, B.; Kamira, M.; Blomme, Guy (Academic Journals, 2017)
Eastern Democratic Republic of Congo constitutes an area where the East African Highland bananas (Musa-AAA-EA) and plantains (Musa-AAB) meet. However, Musa diversity in this region has never been characterized nor represented in national or international collections, yet increasing human activities and build-up of pests and diseases, especially Xanthomonas wilt of banana and banana bunchy top disease, could negatively affect this diversity. This study assessed, collected and morphologically characterized on-farm Musa diversity in the North Kivu and Ituri provinces. Musa accessions collected were added to the UCG-Butembo in situ field collection. A total of 90 and 150 farms were assessed, respectively, in the North Kivu and Ituri provinces. High Musa variability was observed in both provinces. Forty-one cultivars (six presumed new) were identified in Ituri Province compared to 38 cultivars (13 presumed new) in North Kivu Province. Nineteen cultivars occurred in both provinces. Beni and Lubero territories in North Kivu and Mambasa territory in Ituri Province had greater Musa diversity, varying between 27 and 38 cultivars, approximately double of the number of cultivars observed in the other territories. Twenty-three of the 34 Musa descriptors contributed more to the discrimination of the cultivars identified across the provinces and were therefore used for grouping the cultivars using principal component analysis (PCA). The Morisita index of similarity between Ituri Province and North Kivu Province territories was less than 0.5, suggesting dissimilarity in diversity between these sites. Six cultivars: ‘Kirisirya’, ‘Pakuma’, ‘Nziravahima’, ‘Vuhindi’, ‘Tundu’ and ‘Kisubi musa’ were reportedly at risk of genetic erosion.